Case Study: COVID-19 Vaccine Development - Siewert, Stephanie; Kieslich, Katharina; Braun, Matthias; Dabrock, Peter (Springer Science and Business Media B.V., 2023)
When talking about public participation and the regulatory decision-making process, it is crucial to think about the right time and purpose to involve different stakeholders. The chapter explores circumstantial prerequisites for participatory approaches on the basis of a more recent case study: synthetically produced vaccines against the coronavirus SARS-CoV-2. The COVID-19 pandemic made synthetic biology a global issue—in a way that is unprecedented. Yet, its implementation also poses questions for participation for future vaccine and drug production: How can and should we engage the public on ethical questions of emerging and potentially disruptive technologies during a public health emergency? How do certain focus areas, particularly communication and resources, data management and training, provide valuable avenues in dealing with future emergency applications of SB?
CRIS-Team Scopus Importer:2023-04-07
Keywords: Communication; COVID-19; Emergency Authorization; mRNA Vaccine; Pandemic; Resources; Synthetic Vaccines; Training